Pathogenicity of Conidiobolus coronatus and Fusarium solani in mouse models. Issue 6 (27th February 2017) - Li, Yadi; Fang, Xiangang; Zhou, Xiaoqian; Geng, Suying; Wang, Yuxin; Yang, Xiumin
Summary: To study the pathogenicity of Conidiobolus coronatus ( C. coronatus ) and Fusarium solani ( F. solani ) in animal models. Immunocompromised mice were treated with cyclophosphamide and prednisolone via intraperitoneal injection before and after inoculation. According to pathogenic characteristics of different fungi, C. coronatus was used to infect mice via intravenous inoculation, intraperitoneal inoculation, gastrointestinal infusion and intradermal inoculation methods. And F. solani was used to infect mice by inoculation via the abraded or normal skin. In the group of immunocompromised mice, C. coronatus was isolated from the lung tissues of one mouse on day 7 and another on day 10 respectively. The corresponding histopathology revealed infiltration of local inflammatory cells in the lung tissue. Pathogenic lesions were observed in all normal and immunocompromised mice infected with F. solani via abraded skin. The lesions in the immunocompromised mice were more severe and persisted longer than those in the normal mice. Moreover, hyphae were mostly observed in the histopathological examination and fungal culture from the immunocompromised mouse. The pathogenicity of C. coronatus was relatively weak as it did not induce local infections and did not disseminate the disease in immunocompetent and immunocompromised mice. Therefore, F. solani is a type of opportunistic pathogenic fungus, and abraded skin is one of the causative routes of infection.